Multiplicative Connectivity Indices of Tri-Hexagonal Boron Nanotube and Nanotori (Journal of Informatics and Mathematical Sciences, 2019)
A topological index is a numeric value that can be used to characterize some property of the graph representing a molecule. In this article, we compute multiplicative connectivity indices namely, multiplicative version of first Zagreb index \((Π^*_{1})\), second multiplicative Zagreb index \((Π_2)\), first and second multiplicative hyper-Zagreb index \( (H Π_{1}, H Π_2 ) \), general first and second multiplicative Zagreb index \((M Z^a_1, M Z^a_2)\), multiplicative sum-connectivity index \((XΠ)\), multiplicative product-connectivity index \((χ Π)\), multiplicative atom-bond connectivity index \((ABC Π)\) and multiplicative geometric-arithmetic index \((GA Π)\) for tri-hexagonal boron nanotube, tri-hexagonal boron nanotorus and tri-hexagonal boron-\(α\) nanotorus.
Keywords: Multiplicative connectivity indices; Tri-hexagonal boron nanotube; Tri-hexagonal boron nanotorus; Tri-hexagonal boron-\(α\) nanotorus